2009
DOI: 10.1111/j.1365-2133.2008.08974.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin and systemic pharmacokinetics of tacrolimus following topical application of tacrolimus ointment in adults with moderate to severe atopic dermatitis

Abstract: Tacrolimus was primarily partitioned in the skin, with minimal systemic absorption after topical application, in patients with atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 10 publications
5
43
0
3
Order By: Relevance
“…No studies on the use or effect of topical tacrolimus during pregnancy have been published. Systemic absorption of topical tacrolimus is, however, very low in both 0.1% and 0.03% concentrations due to the large size of the molecule, although a very impaired skin barrier as seen in Netherton syndrome may allow absorption . Taken together with the large experience on systemic use of calcineurin inhibitors in organ transplant patients, available data suggest that the risk of congenital defects is not increased.…”
mentioning
confidence: 99%
“…No studies on the use or effect of topical tacrolimus during pregnancy have been published. Systemic absorption of topical tacrolimus is, however, very low in both 0.1% and 0.03% concentrations due to the large size of the molecule, although a very impaired skin barrier as seen in Netherton syndrome may allow absorption . Taken together with the large experience on systemic use of calcineurin inhibitors in organ transplant patients, available data suggest that the risk of congenital defects is not increased.…”
mentioning
confidence: 99%
“…In our study, we analyzed the serum levels of three receptors on CTL and their relative chemokines based on a large sample size. First, local treatment with calcineurin inhibitors did not change the levels of chemokines in serum, which may be due to the minimal systemic exposure of tacrolimus following topical application of tacrolimus ointment . Elevated levels of CCL5, CXCL8 and CXCL10 were observed in the serum of active vitiligo patients, and the levels of CCL5 and CXCL8 were also increased in stable vitiligo patients compared with controls, suggesting that these chemokines may play important roles in the progression and maintenance of vitiligo.…”
Section: Discussionmentioning
confidence: 95%
“…For topical uses of tacrolimus that do not increase systemic blood concentration of the content, systemic tacrolimus levels were negligible when compared with using systemic agents (24,25). Therefore, it is suggested that unknown systemic factors may play a critical role in the local skin healing process, such as diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%